Electron dynamics of unoccupied states in topological insulators - Niesner, Daniel; Otto, Sebastian; Fauster, Thomas; Chulkov, E. V.; Eremeev, S. V.; Tereshchenko, O. E.; Kokh, K. A. (Journal of Electron Spectroscopy and Related Phenomena, 2014)
The topological insulators Bi2Se3 and Bi2Te2Se have been shown to possess unoccupied topological surface states at the center of the surface Brillouin zone at energies around 1.3 eV above the Fermi level. Using time-resolved two-photon photoemission we study the electron dynamics of the unoccupied topological surface states, image-potential states and conduction bands on these surfaces. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Topological insulators; Surface states; Image-potential states; Two-photon photoemission; Electron dynamics